(untitled) (Lafia Journal of Scientific and Industrial Research, 2024)
This study assesses the effects of supplemented diet of Discorea dumenturom on antioxidant status of streptozotocin-induced diabetic rats. Twenty-five adult male wistar rats were randomly assigned into five groups each containing five rats, group two to five were subjected to high fat diet for four weeks and was thereafter induced with STZ intraperitoneally (45mg/kg body weight) resulting to type 2 diabetes. The body weight, glucose concentration and the activities the antioxidant enzymes, Glutathione peroxidase (GPx), Glutathione S-transferase (GST), Catalase (CAT), and Malondialdehyde (MDA) and Glutathione concentration in the kidney, heart and liver were assessed. The Post-treatment with 10% and 20% Yellow Bitter Yam significantly reduced glucose and an healthy reduction in weight in treated groups compared to diabetic controls. In diabetic kidneys, GSH and GST were similar to controls, while GPX, CAT, and MDA decreased. Diabetic hearts showed increased CAT, GSH, and MDA, regulated in the treated group. In diabetic livers, GPx, GST, and MDA were consistent across groups, but GSH and CAT significantly (p>0.05) decreased in post-treated groups. The study suggests Dioscorea dumetorum supplementation regulates antioxidant enzymes, indicating potential hypoglycemic and antioxidative effects, particularly in kidney, heart, and liver enzyme activities associated with Type 2 diabetes.